2022
DOI: 10.3390/agronomy12030672
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Nitrogen Fertilizer Rates Maintained Raspberry Growth in an Established Field

Abstract: Optimizing nitrogen (N) fertilizer rates maintains good red raspberry (Rubus idaeus L.) production while alleviating environmental risks. Although raspberry growers in Washington are using the caneberry nutrient management guides derived from western Oregon, these guides may not be appropriate for other production regions given the differences in climate, soil type, and crop productivity. However, limited research has been conducted to observe the impact of the N fertilizer rate on floricane red raspberry grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
0
6
0
2
Order By: Relevance
“…The chemical composition of fruits depends not only on genetic conditions and the age of plants but also on agrochemical factors, mainly fertilization [42,43]. In this study, the highest yield level was obtained at a dose of 135 kg N•ha −1 , both for the 'Laszka' and 'Glen Ample' cultivars.…”
Section: Influence Of Fertilization On the Size And Quality Of Fruit ...mentioning
confidence: 59%
See 1 more Smart Citation
“…The chemical composition of fruits depends not only on genetic conditions and the age of plants but also on agrochemical factors, mainly fertilization [42,43]. In this study, the highest yield level was obtained at a dose of 135 kg N•ha −1 , both for the 'Laszka' and 'Glen Ample' cultivars.…”
Section: Influence Of Fertilization On the Size And Quality Of Fruit ...mentioning
confidence: 59%
“…Their content was arranged in the following order: Mn > Fe > Zn > Cu > Ni > Cr > C. The authors did not find a significant difference in the concentration of the tested elements in raspberry fruits from organic and conventional cultivation, except for the statistically proven Fe content in organic raspberries. According to Lu et al [43], an increase in the level of nitrogen fertilization as well as an optimal level of hydration provide plants with a higher yield. The authors observed an increase in yields of the 'Norna' and 'Veten' cultivars as a result of irrigation by nearly 52% compared with natural precipitation.…”
Section: Influence Of Fertilization On the Size And Quality Of Fruit ...mentioning
confidence: 99%
“…Many studies have shown that proper reduction in nitrogen fertiliser application increases the yield and improves the nutritional quality of crops. Moreover, it reduces the amounts of wasted nitrogen fertiliser, improves fertiliser utilisation efficiency, and reduces environmental pollution [65]. This study found that under different fertilisation treatments, fruit weight, shape index, and hardness of apples increased with 20% and 30% nitrogen reduction combined with bio-organic fertiliser (Figures 5 and 6), and the fruit yield and nitrogen partial factor productivity also increased accordingly (Figure 7).…”
Section: Discussionmentioning
confidence: 70%
“…Dalam beberapa kasus waktu pemberian pupuk berpengaruh terhadap pertumbuhan maupun hasil dari raspberry. Rempel et al (2004) dan Lu et al (2022) melaporkan bahwa pemberian tunggal di awal atau dengan beberapa kali waktu pemupukan mempengaruhi pertumbuhan, perkembangan tanaman, produksi raspberry, kualitas buah, dan konsentrasi nutrisi pada jaringan daun. Berdasarkan beberapa hasil kajian sebelumnya, maka penelitian ini difokuskan pada dua jenis Rubus yaitu R. rosifolius dan R. fraxinifolius.…”
Section: Pendahuluanunclassified
“…Berbedanya waktu pemberian akan memberikan hasil yang tidak sesuai dengan pertumbuhan tanaman. Lu et al (2022) melaporkan bahwa pengelolaan nutrisi pada tanaman raspberry cukup kompleks, karena bahan organik tanah dan cadangan hara dalam tanaman harus dipertimbangkan sebagai sumber nutrisi potensial. Pertumbuhan floricane dari raspberry menjadi salah satu tantangan pengelolaan nutrisi raspberry dibandingkan dengan tanaman tahunan lainnya, hal tersebut dikarenakan adanya pengaruh waktu pemberian, penyerapan hara dan musim (Rempel et al…”
Section: Perlakuanunclassified